Behavior regulations and motives to participate in physical activity of Finnish team sports athletes - Huang, Houyuan (2014)
The study examined the motivation to participate and behavior regulation in team sports among Finnish athletes. It explored differences across gender and among various team sport types. One hundred and seventy five girls and 142 boys (aged 12 to 24 years old) participated in the study. Motives to participate were measured on the Physical Activity and Leisure Motivation Scale (PALMS, Morris & Rogers, 2004), while behavior regulations were measured on the Behavior Regulation in Sport Questionnaire (BRSQ, Lonsdale, Hodge & Rose, 2008). Others' expectation was excluded from calculations due to low reliability. Participants scored higher on mastery, enjoyment and physical condition in PALMS scales. In regards of behavior regulations, participants reported higher intrinsic regulation, integrated regulation and identified regulation. Sums of scores from both PALMS and BRSQ subscales generally exhibited a simplex pattern ordering. In PALMS, physical condition showed a higher correlation with psychological condition and appearance, while in BRSQ Integrated regulation showed a higher correlation with identified regulation. Comparing between two questionnaires, mastery and physical condition were correlated with identified regulation. An independent sample t-test indicated that girls reported significantly higher means in integrated regulation, mastery, affiliation, physical condition and appearance while boys showed significantly higher means in competition/ego. A one-way between-groups analysis for variance indicated significant differences in PALMS and BRSQ subscales for team ball games participants and aesthetic sports participants. Post- hoc comparisons indicated that aesthetic team sports (e.g., synchronized skating) reported significantly higher means than invasion contact ballgames (e.g., ice-hockey) on item mastery. Aesthetic group also reported significant higher means than invasion non-contact ballgames (e.g., basketball) on item identified regulation, mastery and affiliation. Invasion contact ballgames and invasion non-contact ballgames both showed significantly higher means than aesthetic team sports on item competition/ego. Discussion and conclusion were made and further research direction was suggested.